Cardiovascular applications of magnetic particles - Cicha, Iwona; Alexiou, Christoph (Journal of Magnetism and Magnetic Materials, 2021)
The global burden of atherothrombotic diseases continues to grow. Worldwide, 17.9 million deaths per year are caused by cardiovascular diseases (CVD). According to WHO estimates, this number is expected to grow to more than 23.6 million by 2030. To achieve a more effective primary prevention of cardiovascular morbidity and mortality, the development of new diagnostic and therapeutic strategies is required. Nanomedicine offers a unique platform for novel approaches to the diagnosis and therapy of CVD. In particular iron oxide-based magnetic nanoparticles, a class of nanosized agents with superparamagnetic properties, are considered a promising tool in management of cardiovascular patients. Their possible applications range from plaque imaging and thrombus detection to the targeted drug-delivery, stent endothelialisation and blood vessel regeneration. This paper summarizes recent advances in the implementation of magnetic nanoparticles to diagnosis and treatment of cardiovascular disorders.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Atherosclerosis; Magnetic drug targeting; Magnetic resonance imaging; Stent endothelialization; Superparamagnetic iron oxide nanoparticles; Thrombolysis